Hantavirus Nucleocapsid Protein Has Distinct m(7)G Cap- and RNA-binding Sites - Mir, Mohammad A. (American Society for Biochemistry and Molecular Biology, 2010)
Hantaviruses, members of the Bunyaviridae family, are emerging category A pathogens that carry three negative stranded RNA molecules as their genome. Hantavirus nucleocapsid protein (N) is encoded by the smallest S segment genomic RNA (viral RNA). N specifically binds mRNA caps and requires four nucleotides adjacent to the cap for high affinity binding. We show that the N peptide has distinct cap- and RNA-binding sites that independently interact with mRNA cap and viral genomic RNA, respectively. In addition, N can simultaneously bind with both mRNA cap and vRNA. N undergoes distinct conformational changes after binding with either mRNA cap or vRNA or both mRNA cap and vRNA simultaneously. Hantavirus RNA-dependent RNA polymerase (RdRp) uses a capped RNA primer for transcription initiation. The capped RNA primer is generated from host cell mRNA by the cap-snatching mechanism and is supposed to anneal with the 3′ terminus of vRNA template during transcription initiation by single G-C base pairing. We show that the capped RNA primer binds at the cap-binding site and induces a conformational change in N. The conformationally altered N with a capped primer loaded at the cap-binding site specifically binds the conserved 3′ nine nucleotides of vRNA and assists the bound primer to anneal at the 3′ terminus. We suggest that the cap-binding site of N, in conjunction with RdRp, plays a key role during the transcription and replication initiation of vRNA genome.